2006
DOI: 10.2135/cropsci2006.01-0006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Rate and Mowing Height Effects on TifEagle Bermudagrass Establishment

Abstract: In the southeastern United States, ‘TifEagle’ hybrid bermudagrass [Cynodon dactylon (L). Pers. × C. transvaalensis Burtt Davy] has become a selected cultivar for renovated or new bermudagrass putting greens, and its use has increased in popularity. However, there is limited research which examines TifEagle establishment, especially when cultural practices such as mowing height are included in the experimental design. The objective of this research was to evaluate the impact of N rate and mowing height on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
37
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 27 publications
7
37
2
Order By: Relevance
“…At other times, the PGC of the Zoysiagrass cv. Esmeralda was influenced by N-OMF doses (p ≤ 0.05) (Figure 2), similar to results reported by Lima et al (2010) and Guertal and Evans (2006) for Ber- mudagrass cv. Celebration and the hybrid Bermudagrass cv.…”
Section: Percentage Of Ground Cover By Turfgrass (Pgc)supporting
confidence: 88%
“…At other times, the PGC of the Zoysiagrass cv. Esmeralda was influenced by N-OMF doses (p ≤ 0.05) (Figure 2), similar to results reported by Lima et al (2010) and Guertal and Evans (2006) for Ber- mudagrass cv. Celebration and the hybrid Bermudagrass cv.…”
Section: Percentage Of Ground Cover By Turfgrass (Pgc)supporting
confidence: 88%
“…The interaction eff ects of salinity and mowing on bermudagrass are not well understood. Guertal and Evans (2006) tested the eff ect of diff erent mowing heights (3.2, 3.9, and 4.8 mm) on Tifeagle bermudagrass and concluded that mowing height had less impact on Tifeagle bermudagrass establishment but there was a reduction in turf color and rhizome and stolon weight at the lowest mowing height. Mitchell and Dickens (1979) indicated that mowing height variation from 1.25 to 2.5 cm did not aff ect sod strength of Tifway and Tifgreen bermudagrasses.…”
mentioning
confidence: 99%
“…Mitchell and Dickens (1979) indicated that mowing height variation from 1.25 to 2.5 cm did not aff ect sod strength of Tifway and Tifgreen bermudagrasses. Guertal and Evans (2006) tested the eff ect of diff erent mowing heights (3.2, 3.9, and 4.8 mm) on Tifeagle bermudagrass and concluded that mowing height had less impact on Tifeagle bermudagrass establishment but there was a reduction in turf color and rhizome and stolon weight at the lowest mowing height. No published information is available that addresses the infl uence of mowing height and frequency on bermudagrass salinity tolerance.…”
mentioning
confidence: 99%
“…Establishment and maintaining aesthetics and functional values of bermudagrass greens and tees includes identifying ideal application rates and seasonal applications of fertilizers, topdressing, and frequency of horizontal and vertical mowing and aerification (Bunnell et. al., 2005; Hollingsworth et al, 2005; Guertal and Evans, 2006; Rodriguez et al, 2001; White et al, 2004). After evaluation of vertical mowing and topdressing, management strategies for establishing and established ‘Tifdwarf’, Champion, FloraDwarf, ‘Miniverde’, and TifEagle ultradwarf bermudagrass cultivars in temperate Texas (White et al, 2004) suggested that cultural management will need to change as the cultivars mature.…”
mentioning
confidence: 99%
“…Hollingsworth et al (2005) reported that a high-maintenance schedule that included intensive vertical mowing, topdressing, and aerification during summer months resulted in unacceptable quality for four ultradwarf varieties grown in Auburn, AL. Guertal and Evans (2006) documented that color was reduced when Tif Eagle was mowed at 3.2 mm vs. 3.9 and 4.8 mm. Unruh and Davis (2001) scouted putting greens from 70 golf courses located in Florida, Mississippi, Louisiana, and Alabama.…”
mentioning
confidence: 99%